Using the Timun Mas Folktale to Explore the Depiction of Women in Language Learning: Perspectives from Filipino Students - Aini, Widya; Sarian, Hazen Mellai Xyza; Susanto (IKIP Siliwangi, 2025)
This study examines how Filipino university students perceive the role of women in their culture and their views on the depiction of women in the Indonesian folktale Timun Mas. Studies that explore how students from one country interpret gender roles in traditional stories of another country remain limited, particularly in Southeast Asia. This study addresses that gap by investigating how Filipino students interpret female characters in Timun Mas, providing insight into how cultural narratives influence cross-border perceptions of women. Fifteen students from Mariano Marcos State University participated via open-ended questionnaires. Using a qualitative descriptive method, data were analyzed through Miles and Huberman’s interactive model. The findings revealed four major themes: cultural perception, women’s portrayal in folktales, women’s resistance, and literary reflection. Many Filipino students still associate women with traditional domestic roles, yet an increasing recognition of female strength and independence is evident. The study also demonstrates how a foreign folktale, when used in an English learning context, can prompt cross-cultural dialogue and critical reflection on gender.